Epidemiological Characteristics of Hepatitis C Patients Attending a Tertiary Care Hospital - Kattel, Hari Prasad; Sharma, Sangita; Alfsnes, Kristian; Pathak, Rahul; Rijal, Komal Raj; Ghimire, Prakash; Andreassen, Ashild K; Banjara, Megha Raj (Journal of Nepal Health Research Council, 2024)
Background: Hepatitis C infection is a major public health concern in Nepal. Epidemiological information on hepatitis C virus along with the status of co-infection with hepatitis B virus and human immunodeficiency virus is essential to controlling the hepatitis C burden. The objective of this study was to determine the sero-prevalence of hepatitis C virus infections, proportions of co-infections with human immunodeficiency virus and hepatitis B virus, and identify the demographic characters, and routes of transmission.Methods: A cross-sectional study was conducted from December 2019 to February 2024 at Tribhuvan University Teaching Hospital. The serological tests were performed by enzyme-linked immunosorbent assays from 25133 patients’ serum in four years.Results: The sero-prevalence of hepatitis C virus -infected patients was 0.8% (211/25133). Among them, 6.6% (14/211) were co-infected with human immunodeficiency virus and 1.4% (3/211) with hepatitis B virus. Among 211 hepatitis C virus patients, 174 (82.5%) were male, 156 (73.9%) were young aged 15–47 years with various professions, 167 (79.1%) were literate, and almost one-third of the patients (33.2%, 70/211) were regular alcoholics. Needle sharing among intravenous drug users (45.5%, 96/211) and sexual intercourse (28%, 59/211) were the most common modes of transmission. Conclusions: Although the prevalence of hepatitis C infections is less than 1%, it is more common among young male intravenous drug users. Awareness of the spread of hepatitis C infections among this population needs to be emphasized to control hepatitis C in Nepal.Keywords: characters; co-infection; hepatitis C, sero-prevalence.